(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Welfare concerns are growing regarding surgical castration (SC) in pets, necessitating the need for non-surgical alternatives. Administration of vaccines against gonadotropins releasing hormone (GnRH) have been reported as alternative to SC. This study determined the effect of surgical and immunological castrations (IC) on complete blood counts, plasma testosterone (T), luteinizing hormone (LH) concentrations and ejaculate characteristics in mongrel dogs. Ten intact male dogs were randomly divided into two groups (A & B). Dogs in group A were surgically castrated, while dogs in group B were immunologically castrated with single subcutaneous injection of GnRH vaccine (Improvac®). Blood and semen were collected before SC or IC and fortnightly until sixteen weeks. Blood was analyzed for packed cell volume (PCV), white blood cell count (WBC), haemoglobin concentration (Hb), absolute neutrophil (NEUT) and lymphocyte counts (LYMP), T and LH. Sperm volume (SV), concentration (C), motility (SM), live-dead ratio (LDR) and percentage of abnormal spermatozoa were determined for the semen. Data were presented as mean ± standard deviation and compared using analysis of variance. The PCV and HB of dogs surgically castrated increased progressively up to16th week after castration but only up to10 weeks in dogs immunologically castrated. Both PCV and HB decreased progressively after 10 weeks in dogs immunologically castrated. Similarly, the WBC of dogs surgically castrated steadily increased from 2 weeks up to week 16, while it increased from 6 weeks up to 16 weeks in dogs immunologically castrated. However, PCV, Hb, WBC, NEUT and LYMP did not differ significantly (p > 0.05) between SC and IC. In both groups, the SV, SC, SM, LDR and percentage of abnormal spermatozoa did not differ significantly. It was therefore concluded that there is no significant haematological or endocrinological changes between surgical and immunological castration and that immunological castration may provide safer alternative.